(untitled) (International Journal of Innovative Computing, 2019)
Blockchain, Bitcoin’s core technology, and spinal cord have received enthusiastic attention since the last couple of decades. The Blockchain serves as a paradigm for distributed and unchangeable computations for bitcoins and cryptocurrencies. The key features behind this technology are to create a reliable, secure, transparent, decentralized, and reliable autonomous ecosystem. It is useful for a variety of applications, especially for legacy devices, resources, and infrastructure. In this article, we presented a technical overview, its application, and the challenges associated with blockchain technology and cryptocurrencies. This study aims to provide a ground-breaking overview and future research direction and promising importance of Blockchain.